経下顎舌縦割進入法で手術支援を行った上位脊椎腫瘍の1例 - 河奈, 裕正; 加藤, 伸; 莇生田, 整治; 中川, 種昭; 小池, 晶彦; 小山, 慶介 (日本口腔外科学会雑誌, 2010)
Although surgery for upper spinal tumors is usually performed via a posterior approach, a transoral approach from the anterior direction is necessary if the tumor is too big to extirpate via the posterior approach alone. To obtain a good anterior view of the surgical field, the mandible, tongue, and soft palate have to be split in some patients. Oral and maxillofacial surgeons thus play an important role in such procedures. We report the case of a 66-year-old woman who presented with neck pain. The diagnosis was chordoma of the second centrum, and the patient was referred to the Department of Orthopedics of our hospital by an orthopedic clinic. Computed tomography and magnetic resonance imaging indicated that the tumor was located at the level of C2 and spread to the lower part of C3, destroying the bone. The orthopedic surgical team decided to employ both posterior and anterior approaches and invited our department to assist in the transoral anterior approach. Vertical splitting of the mandible, incising the skin of the mental region and splitting the middle of the tongue were extremely effective as supportive procedures for an anterior approach to the spinal tumor.